A case of abdominal pregnancy following in vitro fertilization and embryo transfer treated with laparoscopic surgery - Shinsuke Koyama; Ai Yoshino; Koichiro Okuno; Hirokazu Naoi; Masahiro Watanabe; Kimiaki Ozaki; Yasuhiko Shiki (Wolters Kluwer Medknow Publications, 2016)
It is well known that the incidence of ectopic pregnancy has increased significantly with the prevalence of assisted reproductive technologies such as in vitro fertilization and embryo transfer (IVF-ET). Almost all ectopic pregnancies following IVF-ET are actually tubal pregnancies just like ectopic pregnancy following natural conception. Abdominal pregnancy is a rare form of ectopic pregnancy (< 1% of all ectopic pregnancies) and therefore abdominal pregnancy following IVF-ET is very rare. Recently, we experienced a case of abdominal pregnancy following IVF-ET treated with laparoscopic surgery at 10 weeks' gestation. The possibility of an ectopic pregnancy including abdominal and heterotopic pregnancies should be considered in any pregnant woman following IVF-ET. A diagnostic laparoscopy is a very suitable procedure for looking into the abdominal cavity in case of such a rare ectopic pregnancy.